Issuer-oriented underpricing costs in initial public offers: Evidence from Hong Kong - Leung, Jeffery; Menyah, Kojo (Journal of Corporate Finance, 2006)
This paper estimates the underpricing cost associated with new shares issued and sold when firms go public in a traditional British-style IPO market in contrast to prior work which focussed on the underpricing cost to pre-IPO investors. Secondly, the estimates account for interest income on application funds received by issuing firms. Using data from the Hong Kong IPO market, the results show that the issuer underpricing cost of new share issues is on average only 14% of headline underpricing. When interest on application funds is taken into account, net issuer underpricing cost reduces to just around 7% of headline underpricing. This finding provides a compelling explanation of why issuing companies may not be concerned about underpricing in traditional British-style IPO markets. Thirdly, we also find that pre-IPO investors take steps to minimise wealth transfer to new investors either by selling a very small proportion or none of their pre-IPO shares. These findings suggest that explanations of IPO underpricing to the various parties involved in the process should, in part, be sought in the institutional structures and investment banking practices of the relevant primary capital market.